Sunflower Seed Oil Enriched with Compounds from the Turmeric Rhizome: Extraction, Characterization and Cell Viability - Késia Corsato de Oliveira Segantini; Oscar de Oliveira Santos Junior; Vitor Augusto Dos Santos Garcia; Djéssica Tatiane Raspe; Camila da Silva (Separations)
The present work aimed to obtain and characterize sunflower seed oil (SO) enriched with compounds from turmeric rhizome (TR). For this purpose, the enriched oil was obtained from two strategies: extraction of the compounds from TR using SO as solvent (ESO) and simultaneous extraction of SO and TR compounds using ethyl acetate as solvent (ESOS). In these strategies, the effect of time (15 and 30 min) and temperature (60 and 70 °C) on the enrichment in relation to the curcuminoids content was determined. Evaluation of phytochemicals such as total phenolic compounds (TPCs), phenolic compound profile and fatty-acid profile and bioactivity by antioxidant potential (AP) was carriedoutin the enriched oils and in the SO;mean while, oxidative stability and cytotoxicity were evaluated using HaCaT (human immortalized keratinocyte) cells. From the results obtained, higher contents of curcuminoids (510 mg/100 g oil) were observed in the oil obtained from simultaneous extraction (ESOS) in a shorter time and lower temperature (15 min and 60 °C), and similar behavior was found for the content of phenolic compounds and antioxidant potential. The profile of phenolic compounds revealed the presence of phenolic acids, curcuminoids and terpenes in the composition of the enriched oils, which increased oxidative stability. The oils obtained did not show any cytotoxic effect against the cells tested, confirmed by the high survival rate (>88%) after 48 h of exposure.